Penyuluhan kesehatan gigi dan mulut menggunakan media poster pada siswa Sekolah Dasar - Utari Zulkaidah; Rezki Dirman; Sultan Amin Yasin; Supiana Supiana (JOURNAL of Public Health Concerns, 2026)
Background: Oral health is a crucial component of general health that supports a child's growth and development. However, oral diseases particularly dental caries remain prevalent health issues among school-aged children. Purpose: To enhance students' knowledge regarding oral hygiene and the prevention of oral diseases through the use of posters. Method: The community service activity was carried out on Saturday, April 18, 2026, at Elementary School 34 Paconne, North Belopa District, Luwu Regency, South Sulawesi. The initiative aimed to impart knowledge and teach oral hygiene practices to children, involving 40 students from SD 34 Paconne as participants. Knowledge levels were assessed using questionnaires administered before (pre-test) and after (post-test) the educational session. Evaluation was carried out through direct observation and descriptive analysis, comparing pre-test and post-test scores regarding oral health. Results: A shift in students' knowledge levels was observed following the poster-based educational activity; students participated enthusiastically, engaged actively in the Q&A session, and successfully demonstrated correct tooth-brushing techniques. There was a marked improvement in the students' oral health knowledge: the proportion of students with a "good" level of knowledge rose from 20.0% prior to the activity to 75.0% afterward. Conclusion: The educational activity regarding oral hygiene and the prevention of oral diseases, utilizing posters as a medium, proved highly effective among elementary school students. The activity was successfully conducted and received a positive response from the students. Posters helped enhance the students' knowledge of oral health, while demonstrations and a mass tooth-brushing session provided hands-on practical experience. This activity is expected to foster oral hygiene habits among elementary school students from an early age. Suggestion: It is recommended that similar activities be conducted on a continuous basis and integrated with the School Dental Health Program (UKGS) in elementary schools. This approach aims to instill healthy lifestyle habits early on, ensuring long-term benefits. Keywords: Dental disease prevention; Health education; Oral health; Posters Pendahuluan: Kesehatan gigi dan mulut merupakan bagian penting dari kesehatan umum yang berperan dalam mendukung pertumbuhan dan perkembangan anak. Namun, penyakit gigi dan mulut, terutama karies gigi, masih menjadi masalah kesehatan yang banyak ditemukan pada anak usia sekolah. Tujuan: Untuk meningkatkan pengetahuan siswa mengenai pemeliharaan dan pencegahan penyakit gigi dan mulut melalui media poster. Metode: Kegiatan pengabdian masyarakat dilaksanakan pada hari Sabtu, 18 April 2026 di Sekolah Dasar 34 Paconne, Kecamatan Belopa Utara, Kabupaten Luwu, Sulawesi Selatan. Sasaran kegiatan ini adalah memberikan pengetahuan dan cara menjaga kesehatan gigi dan mulut pada anak. Melibatkan 40 siswa SD 34 Paconne untuk menjadi responden. Penilaian tingkat pengetahuan responden menggunakan kuesioner yang diberikan sebelum kegiatan edukasi (pre-test) dan setelah kegiatan edukasi (post-test). Evaluasi dilakukan melalui observasi langsung dan secara deskriptif dengan melihat peningkatan pengetahuan responden antara nilai pre-test terhadap nilai post-test terkait kesehatan gigi dan mulut dalam kegiatan pengabdian ini. Hasil: Adanya perubahan tingkat pengetahuan siswa sebelum dan sesudah dilakukan kegiatan edukasi menggunakan media poster, siswa mengikuti kegiatan dengan antusias, aktif dalam sesi tanya jawab, serta mampu mempraktikkan teknik menyikat gigi yang benar. Terdapat peningkatan pengetahuan responden tentang kesehatan gigi dan mulut, dimana responden yang memiliki pengetahuan dalam kategori baik sebelum kegiatan edukasi hanya sebesar 20.0% dan setelah kegiatan edukasi menjadi sebesar 75.0%. Simpulan: Kegiatan penyuluhan pemeliharaan dan pencegahan penyakit gigi dan mulut menggunakan media poster sangat efektif pada siswa Sekolah Dasar. Kegiatan terlaksana dengan baik dan mendapat respons positif dari siswa. Media poster membantu meningkatkan pengetahuan siswa mengenai kesehatan gigi dan mulut, sedangkan demonstrasi dan sikat gigi massal memberikan pengalaman praktik secara langsung. Kegiatan ini diharapkan dapat mendukung terbentuknya perilaku pemeliharaan kesehatan gigi dan mulut sejak dini pada siswa Sekolah Dasar. Saran: Diharapkan kegiatan serupa perlu dilaksanakan secara berkelanjutan dan diintegrasikan dengan program Usaha Kesehatan Gigi Sekolah (UKGS) di Sekolah Dasar agar dapat menanamkan pola hidup sehat sejak dini sehingga dampaknya dapat dirasakan secara jangka panjang.